Advances in Distillation Retrofit - Long, Nguyen Van Duc; Lee, Moonyong (Springer Singapore : Imprint: Springer, 2017)
This book describes the current state of the art in the retrofit of existing distillation processes using advanced distillation techniques. Highlighting concept and practical application rather than theory, it emphasizes the use of advanced process integration and intensification techniques, such as multi-effect distillation, heat pump assisted distillation, thermally coupled distillation, dividing wall column, reactive distillation, and innovative hybrid systems. As a thermal separation method, distillation is one of the most important and widely used technologies in the chemical process industry. While it has many advantages, one major drawback is its large energy requirement, which can significantly influence overall plant profitability. The increasing cost of energy has forced industry to reduce its energy requirement, but simultaneously there has been a need to increase capacity and output due to heightened demand. To accomplish this, the retrofit of distillation processes to increase efficiency and output has become a crucial issue. This book describes the use of advanced process integration and process intensification techniques to carry out effective distillation retrofit. Written by leading researchers in distillation process, process integration, process intensification, and process retrofit, the book presents a comprehensive review of contemporary advanced distillation techniques which can be employed in grass-root systems and retrofit. It is a valuable source of information for undergraduate and postgraduate students of chemical engineering, practicing process designers and chemical engineers.
Keywords: Chemistry.; Chemical engineering.; Industrial engineering.; Production engineering.; elektronické knihy; electronic books